Experimental study on noise reduction effect of installing concrete deck on existing steel girders - Saito, Masamichi; Sugimoto, Ichiro; Sasaki, Eiichi (International Journal of Steel Structures, 2015)
There are a number of existing steel railway bridges which has problems regarding structure-borne noise under train passage. Authors have proposed a performance improvement method of existing steel railway bridges by installing concrete deck. By this method, the vibration of the girder and the structure-borne noise are expected to be reduced. Generally, it is known that concrete deck can reduce the vibration and the noise. However, the noise reduction effect has not been clarified. In this study, impact hammer tests were carried out to figure out the reduction effect of the concrete deck on the vibration and the noise. Through the test, it was found that the response acceleration of the steel girder web was reduced by installing the concrete deck, as a result of reducing the propagation of on-girder vibration into the steel girder.